15⋅(4d-1)=7

Multiply both sides of the equation by 5.

5⋅15⋅(4d-1)=5⋅7

Simplify 5⋅15⋅(4d-1).

Cancel the common factor of 5.

Cancel the common factor.

5⋅15⋅(4d-1)=5⋅7

Rewrite the expression.

1⋅(4d-1)=5⋅7

1⋅(4d-1)=5⋅7

Multiply 4d-1 by 1.

4d-1=5⋅7

4d-1=5⋅7

Multiply 5 by 7.

4d-1=35

4d-1=35

Add 1 to both sides of the equation.

4d=35+1

Add 35 and 1.

4d=36

4d=36

Divide each term in 4d=36 by 4.

4d4=364

Cancel the common factor of 4.

Cancel the common factor.

4d4=364

Divide d by 1.

d=364

d=364

Divide 36 by 4.

d=9

d=9

Solve for d 1/5*(4d-1)=7